1. The problem statement, all variables and given/known data T(a0 + a1t+a2t2) = 3a0 + (5a0 - 2a1)t + (4a1 + a2)t2 Find the image of the vectors : 1. 1 2. t 3. t2 2. Relevant equations T(a0 + a1t+a2t2) = 3a0 + (5a0 - 2a1)t + (4a1 + a2)t2 3. The attempt at a solution I don't know how my book solves these transformations, but the answers are: T(1) = 3+5t T(t) = -2t+4t2 T(t2) = t2 How do you substitute a single vector for an entire expression to solve for each of these? When it was a simple transformation (T(x) = x^2), you just replace x with the input, but for this one, you have to substitute an entire expression to find the transformation.